Evaluate the following expression without using trigonometric tables:
${\sin ^2}{28^ \circ } + {\sin ^2}{62^ \circ } + {\tan ^2}{38^ \circ } - {\cot ^2}{52^ \circ } + \dfrac{1}{4}{\sec ^2}{30^ \circ }$
Answer
Verified
510.6k+ views
Hint: Let’s arrange sin terms and tan terms together and use formulae $\sin \left( {{{90}^ \circ } - \theta } \right) = \cos \theta $ and $\tan \left( {{{90}^ \circ } - \theta } \right) = \cot \theta $ and then simplify further.
Complete step-by-step answer:
Let the value of the given expression be $k$. Then:
$k = {\sin ^2}{28^ \circ } + {\sin ^2}{62^ \circ } + {\tan ^2}{38^ \circ } - {\cot ^2}{52^ \circ } + \dfrac{1}{4}{\sec ^2}{30^ \circ }$
This can be rearranged as:
$k = \left( {{{\sin }^2}{{28}^ \circ } + {{\sin }^2}{{62}^ \circ }} \right) + \left( {{{\tan }^2}{{38}^ \circ } - {{\cot }^2}{{52}^ \circ }} \right) + \dfrac{1}{4}{\sec ^2}{30^ \circ }$
We know that $\sin \left( {{{90}^ \circ } - \theta } \right) = \cos \theta $ and $\tan \left( {{{90}^ \circ } - \theta } \right) = \cot \theta $, using these two formulae, we’ll get:
$
\Rightarrow k = \left( {{{\sin }^2}{{28}^ \circ } + {{\sin }^2}\left( {{{90}^ \circ } - {{28}^ \circ }} \right)} \right) + \left( {{{\tan }^2}{{38}^ \circ } - {{\cot }^2}\left( {{{90}^ \circ } - {{38}^ \circ }} \right)} \right) + \dfrac{1}{4}{\sec ^2}{30^ \circ }, \\
\Rightarrow k = \left( {{{\sin }^2}{{28}^ \circ } + {{\cos }^2}{{28}^ \circ }} \right) + \left( {{{\tan }^2}{{38}^ \circ } - {{\tan }^2}{{38}^ \circ }} \right) + \dfrac{1}{4}{\sec ^2}{30^ \circ }, \\
\Rightarrow k = \left( {{{\sin }^2}{{28}^ \circ } + {{\cos }^2}{{28}^ \circ }} \right) + 0 + \dfrac{1}{4}{\sec ^2}{30^ \circ } \\
$
As we know that, ${\sin ^2}\theta + {\cos ^2}\theta = 1$ , and $\sec {30^ \circ } = \dfrac{2}{{\sqrt 3 }}$.
Applying these results, we have:
$
\Rightarrow k = 1 + \dfrac{1}{4}{\left( {\dfrac{2}{{\sqrt 3 }}} \right)^2}, \\
\Rightarrow k = 1 + \dfrac{1}{4} \times \dfrac{4}{3}, \\
\Rightarrow k = 1 + \dfrac{1}{3}, \\
\Rightarrow k = \dfrac{4}{3} \\
$
Substituting the value of $k$, we’ll get:
${\sin ^2}{28^ \circ } + {\sin ^2}{62^ \circ } + {\tan ^2}{38^ \circ } - {\cot ^2}{52^ \circ } + \dfrac{1}{4}{\sec ^2}{30^ \circ } = \dfrac{4}{3}$
Thus, the value of the given expression is $\dfrac{4}{3}$.
Note: If any of the trigonometric expression contains $\sin {\theta _1},\cos {\theta _2}$ together or $\tan {\theta _1},\cot {\theta _2}$ together or $\sec {\theta _1},\cos ec{\theta _2}$ together such that ${\theta _1} + {\theta _2} = {90^ \circ }$, then we can always use following results for simplification:
$
\sin \theta = \cos \left( {90 - \theta } \right), \\
\tan \theta = \cot \left( {90 - \theta } \right), \\
\sec \theta = \cos ec\left( {90 - \theta } \right) \\
$
Complete step-by-step answer:
Let the value of the given expression be $k$. Then:
$k = {\sin ^2}{28^ \circ } + {\sin ^2}{62^ \circ } + {\tan ^2}{38^ \circ } - {\cot ^2}{52^ \circ } + \dfrac{1}{4}{\sec ^2}{30^ \circ }$
This can be rearranged as:
$k = \left( {{{\sin }^2}{{28}^ \circ } + {{\sin }^2}{{62}^ \circ }} \right) + \left( {{{\tan }^2}{{38}^ \circ } - {{\cot }^2}{{52}^ \circ }} \right) + \dfrac{1}{4}{\sec ^2}{30^ \circ }$
We know that $\sin \left( {{{90}^ \circ } - \theta } \right) = \cos \theta $ and $\tan \left( {{{90}^ \circ } - \theta } \right) = \cot \theta $, using these two formulae, we’ll get:
$
\Rightarrow k = \left( {{{\sin }^2}{{28}^ \circ } + {{\sin }^2}\left( {{{90}^ \circ } - {{28}^ \circ }} \right)} \right) + \left( {{{\tan }^2}{{38}^ \circ } - {{\cot }^2}\left( {{{90}^ \circ } - {{38}^ \circ }} \right)} \right) + \dfrac{1}{4}{\sec ^2}{30^ \circ }, \\
\Rightarrow k = \left( {{{\sin }^2}{{28}^ \circ } + {{\cos }^2}{{28}^ \circ }} \right) + \left( {{{\tan }^2}{{38}^ \circ } - {{\tan }^2}{{38}^ \circ }} \right) + \dfrac{1}{4}{\sec ^2}{30^ \circ }, \\
\Rightarrow k = \left( {{{\sin }^2}{{28}^ \circ } + {{\cos }^2}{{28}^ \circ }} \right) + 0 + \dfrac{1}{4}{\sec ^2}{30^ \circ } \\
$
As we know that, ${\sin ^2}\theta + {\cos ^2}\theta = 1$ , and $\sec {30^ \circ } = \dfrac{2}{{\sqrt 3 }}$.
Applying these results, we have:
$
\Rightarrow k = 1 + \dfrac{1}{4}{\left( {\dfrac{2}{{\sqrt 3 }}} \right)^2}, \\
\Rightarrow k = 1 + \dfrac{1}{4} \times \dfrac{4}{3}, \\
\Rightarrow k = 1 + \dfrac{1}{3}, \\
\Rightarrow k = \dfrac{4}{3} \\
$
Substituting the value of $k$, we’ll get:
${\sin ^2}{28^ \circ } + {\sin ^2}{62^ \circ } + {\tan ^2}{38^ \circ } - {\cot ^2}{52^ \circ } + \dfrac{1}{4}{\sec ^2}{30^ \circ } = \dfrac{4}{3}$
Thus, the value of the given expression is $\dfrac{4}{3}$.
Note: If any of the trigonometric expression contains $\sin {\theta _1},\cos {\theta _2}$ together or $\tan {\theta _1},\cot {\theta _2}$ together or $\sec {\theta _1},\cos ec{\theta _2}$ together such that ${\theta _1} + {\theta _2} = {90^ \circ }$, then we can always use following results for simplification:
$
\sin \theta = \cos \left( {90 - \theta } \right), \\
\tan \theta = \cot \left( {90 - \theta } \right), \\
\sec \theta = \cos ec\left( {90 - \theta } \right) \\
$
Recently Updated Pages
What percentage of the area in India is covered by class 10 social science CBSE
The area of a 6m wide road outside a garden in all class 10 maths CBSE
What is the electric flux through a cube of side 1 class 10 physics CBSE
If one root of x2 x k 0 maybe the square of the other class 10 maths CBSE
The radius and height of a cylinder are in the ratio class 10 maths CBSE
An almirah is sold for 5400 Rs after allowing a discount class 10 maths CBSE
Trending doubts
The Equation xxx + 2 is Satisfied when x is Equal to Class 10 Maths
Why is there a time difference of about 5 hours between class 10 social science CBSE
Change the following sentences into negative and interrogative class 10 english CBSE
Write a letter to the principal requesting him to grant class 10 english CBSE
Explain the Treaty of Vienna of 1815 class 10 social science CBSE
Write an application to the principal requesting five class 10 english CBSE